LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING PADA MATERI KINGDOM ANIMALIA - Imroatul Murodatusy Syajaroh; Sumiyati Sa’adah; Mar’atus Sholikha (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
Ideal learning affects the achievement of learning objectives. To achieve this goal, innovative learning media are needed to develop student’s skills in finding concept based on discovery learning. The purpose of this research is to describe the development stage, analyse feasibility, analyse readability, and describe student responses. This study applies the Research and Development 3D model (define, design, develop). The results of the research reveal that the define includes the analysis of the initial end, students, assignments, concepts, and learning objectives. Design includes working on the support criteria, media determination, format, and initial design. Develop includes validation, LKPD readability test, and response test. The average validation reached 85,2% (very decent), readability reached 3,94% in the very good category, and the response percentage was 85,8% (very strong). Thus, Discovery Learning-based worksheets on Animalia kingdom material are feasible to be applied as learning media.